Perbandingan Nilai Indeks Green dan King antara Anemia Defisiensi Besi dengan Thalassemia - Astri Pinilih; Syuhada Syuhada; Zulhafis Mandala; Dianthy Novia (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: The definitive differential diagnosis between Thalassemia and iron deficiency anemia is based on the results of HbA₂ electrophoresis, serum iron levels, and ferritin calculations. The purpose of using indices is to distinguish and detect subjects with high probability who need appropriate follow-up and to reduce unnecessary investigative costs. Objective: To determine the difference in the value of the Green & King Index between Iron Deficiency Anemia patients and Thalassemia patients in Abdul Moeloek Regional Hospital in Lampung Province in 2019. Method: This research is a quantitative study with a comparative test by taking secondary data. With the number of samples using a ratio of 1: 1 so that there were 152 people with iron deficiency anemia and 152 people with Thalassemia. Results: The results of statistical analysis using the Mann Whitney U test showed a p-value for comparison of the Green & King index values ​​between iron deficiency anemia patients and thalassemia patients of 0,000 (p <0.05). Conclusion: There is a significant difference in the value of the Green & King index between iron deficiency anemia patients and thalassemia patients in Abdul Moeloek Regional Hospital Lampung Province.